Long non-coding RNA UCA1 can predict tumor lymph node metastasis - Yuan-Hang Wang; Fang Wang; Lan Zhang; Jia-Chun Lu (Tumor Biology, 2017)
Numerous studies suggested that long non-coding RNA UCA1 was highly expressed and played critical roles in the development and progression of various cancerous tissues and cells. However, little is known about the association between UCA1 and tumor lymph node metastasis. In our study, a systematic review was conducted to evaluate the association between UCA1 expression and tumor lymph node metastasis and explore whether UCA1 can be a potential molecular marker for predicting the multiple tumor lymph node metastasis. The meta-analysis result showed that the number of lymph node metastasis in different tumorous types of UCA1 high-expression group was significantly higher compared with UCA1 low-expression group (pooled odds ratio = 2.13, 95% confidence interval: 1.60–2.84, p < 0.05). To verify whether the above result was still valid in specific tumor type, we conducted a meta-analysis including four articles on colorectal cancer (pooled odds ratio = 2.07, 95% confidence interval: 1.28–3.34, p < 0.05). Based on the existing results, it can be explained that the long non-coding RNA UCA1 was significantly associated with lymph node metastasis and both the results revealed that compared with UCA1 low-expression group, the lymph node metastasis rate of UCA1 high-expression group was statistically significantly elevated. Therefore, long non-coding RNA UCA1 has the potential of being a biological marker for predicting lymph node metastasis.